2019
DOI: 10.1111/jcpe.13185
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic signalling mechanisms and early implant healing phases in healthy versus generalized aggressive periodontitis patients: A prospective, case–control study

Abstract: Aims Periodontal diseases negatively affect implant osseointegration. Perturbations in non‐neuronal cholinergic signalling mechanisms are associated with periodontitis; however, their role in generalized aggressive periodontitis (GAgP) is unknown. The aim of this prospective case–control study was to determine the relationship between non‐neuronal cholinergic signalling mechanisms, secreted Ly‐6/uPAR‐related protein‐1 (SLURP‐1), interleukin‐17 (IL‐17) family cytokines and healing of dental implants in health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…8 Periodontal diseases such as aggressive periodontitis negatively affect implant osseointegration. 9 Thus, clinicians should save such teeth rather than extract them and replace them with implants. 10 Comparing the survival rate between endodontically treated teeth with poor prognosis and implants placed in previously diseased sites showed that the survival rate of endodontically treated teeth was comparatively higher than implants.…”
Section: Introductionmentioning
confidence: 99%
“…8 Periodontal diseases such as aggressive periodontitis negatively affect implant osseointegration. 9 Thus, clinicians should save such teeth rather than extract them and replace them with implants. 10 Comparing the survival rate between endodontically treated teeth with poor prognosis and implants placed in previously diseased sites showed that the survival rate of endodontically treated teeth was comparatively higher than implants.…”
Section: Introductionmentioning
confidence: 99%